ANALISIS YURIDIS HAK ULAYAT TERHADAP KEPEMILIKAN TANAH ADAT BERDASARKAN UNDANG-UNDANG NOMOR 5 TAHUN 1960 TENTANG PERATURAN DASAR POKOK-POKOK AGRARIA - Ni Komang Putri Sari Sunari Wangi; Komang Febrinayanti Dantes; Ketut Sudiatmaka (Jurnal Ilmu Hukum Sui Generis, 2023)
The purpose of this research is to explore the application of customary rights in relation to customary land ownership of indigenous peoples. In particular, the focus is on the interpretation and analysis of Law Number 5 of 1960 which regulates the Basic Agrarian Regulations. This study aims to examine the level of legal protection given to customary law community customary rights as stipulated in Law Number 5 of 1960. The research methodology used in this research is normative legal research with statutory and conceptual approaches. The legal sources used include primary law, secondary law, and tertiary law. By using this research method and examining relevant legal sources, this research seeks to deepen understanding of the legal framework around customary rights and their relationship to customary land ownership of indigenous peoples. This research uses a descriptive approach, specifically using library research techniques to collect, read, study, and analyze legal materials. This technique involves gathering legal material and making use of the findings in research. The discussion emphasizes the existence and enforcement of legal protection of customary rights. Recognition and respect for customary law community units and their traditional rights, as outlined in Article 18B Paragraph 2 of the 1945 Constitution, plays an important role in providing this protection. This constitutional provision recognizes the importance of customary law communities and their rights, as long as they are in line with the development of society and the principles of the Unitary State of the Republic of Indonesia, which are further regulated by law.